Reversal of Multidrug Resistance in Cancer by Multi-Functional Flavonoids - Ye, Qingmei; Liu, Kai; Shen, Qun; Li, Qingyue; Hao, Jinghui; Han, Fangxuan; Jiang, Ren-Wang (Frontiers in Oncology, 2019)
Multidrug resistance (MDR) resulting from different defensive mechanisms in cancer is one of the major obstacles of clinical treatment. To circumvent MDR many reversal agents have been developed, but most of them failed in clinical trials due to severely adverse effects. Recently, certain natural products have been reported to overcome MDR, including flavonoids which are abundant in plants, foods and herbs. Structure of flavonoids can be abbreviated as C6-C3-C6 (C for carbon), and further categorized into flavonoids, iso-flavonoids, neo-flavonoids according to their structural backbones. Flavonoids possess multiple bioactivities, and a growing body of research has indicated that both flavonoids and iso-flavonoids can either kill or re-sensitize conventional chemotherapeutics to resistant cancer cells. Here, we summarize the research and discuss the underlying mechanisms, concluding that these flavonoids do not function as specific regulators of target proteins, but rather as multi-functional agents that negatively regulate the key factors contributing to MDR.